Elucidating the adaptation and temporal coordination of metabolic pathways using in-silico evolution - Gottstein, Willi; Müller, Stefan; Herzel, Hanspeter; Steuer, Ralf (Biosystems, 2014)
Cellular metabolism, the interconversion of small molecules by chemical reactions, is a tightly coordinated process that requires integration of diverse environmental and intracellular cues. While for many organisms the topology of the network of metabolic reactions is increasingly known, the regulatory principles that shape the network's adaptation to diverse and changing environments remain largely elusive. To investigate the principles of metabolic adaptation and regulation in metabolic pathways, we propose a computational approach based on in-silico evolution. Rather than analyzing existing regulatory schemes, we let a population of minimal, prototypical metabolic cells evolve rate constants and appropriate regulatory schemes that allow for optimal growth in static and fluctuating environments. Applying our approach to a small, but already sufficiently complex, minimal system reveals intricate transitions between metabolic modes. These results have implications for trade-offs in resource allocation. Going from static to varying environments, we show that for fluctuating nutrient availability, active metabolic regulation results in a significantly increased overall rate of metabolism.
Keywords: Evolution, Molecular; fyziologická adaptace; signální transdukce; Computer Simulation; Humans; biologické hodiny; Models, Genetic; algoritmy; Algorithms; Signal Transduction; Biological Clocks; počítačová simulace; modely genetické; Metabolome; Adaptation, Physiological; lidé; molekulární evoluce; metabolom; Metabolic Flux Analysis; analýza metabolického toku; Animals; zvířata